Effect of particulate matter (PM 10) pollutant concentration on peak expiratory flow rate score in junior high school students - Niken Sawitri; Oma Rosmajudi; Dedi Subardja; Heda Melinda D N (Indonesian Pediatric Society Publishing House, 2016)
Background Various pollutants especially particulate matter with diameter of 10 micrometer or less (PM 10) reduce the function of lung. However, its effect to peak expiratory flow rate (PEFR) as a parameter of central airway resistance is still inconsistent. Objective This study was designed to assess the impact of differ- ent PM 10 concentration to PEFR score among junior high school students who live in two areas. Methods It was a descriptive analytical study with cross sectional design to junior high school students who lived in areas with high PM 10 i.e, Cililin sub district (252.63 mg/m 3 /h) and low PM 10 i.e., Paseh sub district (27.15 mg/m 3 /h). PEFR was measured by using Mini Wright Peak Flow Meter and body weight by microtoire. Data of indoor pollutants were collected from questionnaires. Results There were 463 subjects, 242 students in Cililin and 221 students in Paseh, who fulfilled the inclusion criteria which were aged 12 -15 years, living more than one years continuously within radius of 5 km from the location of pollutant measurement, non smokers, and considered "health" according to history taking and physical examination. The PEFR score in Cililin (305.9+57.9 l/min) was significantly lower than that in Paseh (327.7+54.8 l/min (t=4.15; p<0.001)). Conclusion Although the influence of indoor pollutants especially cooking stoves could not be ignored, the difference of PEFR score in these two groups were possibly due to the different concentra- tion of PM 10